1995
DOI: 10.1002/ijc.2910630220
|View full text |Cite
|
Sign up to set email alerts
|

Decreased biotolerability for ivermectin and cyclosporin a in mice exposed to potent P‐glycoprotein inhibitors

Abstract: SDZ PSC 833 or SDZ 280-446 are strong blockers of the function of class I mdr gene-encoded P-glycoprotein molecules, which were developed for the reversal of multi-drug-resistance of tumor cells. When treated with such drugs, normal mice may display hypersensitivity to cyclosporin A and ivermectin. The recorded signs of acute toxicity are compatible with alterations of the murine central nervous system functions and with earlier data suggesting that P-glycoprotein expressed at the murine blood-brain barrier mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
26
0
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 16 publications
3
26
0
1
Order By: Relevance
“…Current clinical trials aimed at treating multidrug resistant cancer using effective P-gp inhibitors should thus be cautiously monitored for inadvertant CNS toxicity of any of the drugs concomitantly administered to the patients. For example, Didier and Loor (43) found that oral coadministration of PSC833 increased the sensitivity of mice to ivermectin more than tenfold, although this study did not measure directly whether the increase in toxicity was mainly due to increased plasma levels, or increased brain/plasma ratios for ivermectin.…”
Section: Discussionmentioning
confidence: 87%
“…Current clinical trials aimed at treating multidrug resistant cancer using effective P-gp inhibitors should thus be cautiously monitored for inadvertant CNS toxicity of any of the drugs concomitantly administered to the patients. For example, Didier and Loor (43) found that oral coadministration of PSC833 increased the sensitivity of mice to ivermectin more than tenfold, although this study did not measure directly whether the increase in toxicity was mainly due to increased plasma levels, or increased brain/plasma ratios for ivermectin.…”
Section: Discussionmentioning
confidence: 87%
“…In fact, a number of in vivo proof-ofprinciple studies in animals have been undertaken using several different inhibitors of P-glycoprotein and various probe drugs. For example, drug brain levels relative to those in blood plasma of digoxin (Mayer et al, 1997, Song et al, 1999 and nelfinavir (Choo et al, 2000) were increased in mice pretreated with valspodar , and the neurotoxicities of ivermectin and cyclosporin A were greater following administration of the modulator (Didier and Loor, 1995). Similar studies have been reported with more recently developed inhibitors with increased potency, such as elacridar (GF-120918) and various drugs (Letrent et al, 1998(Letrent et al, , 1999Kemper et al, 2003Kemper et al, , 2004b.…”
mentioning
confidence: 99%
“…Mdrla gene-knockout mice treated with the neurotoxic pesticide ivermectin demonstrated increased sensitivity to this pesticide and increased accumulation of this pesticide in the brain as compared to control mice (7). When C57BL/6 mice were cotreated with ivermectin and the P-gp inhibitors SDZ PSC833 or SDZ 280-446, the mice were hypersensitive to the neurotoxic effects of ivermectin compared to treatment with ivermectin alone (8). Additionally, rats treated with the pesticide chlorpyrifos showed increased P-gp protein levels in the bile duct, adrenal gland, stomach, jejunum, and kidney proximal tubules (9).…”
mentioning
confidence: 99%